Entrepreneurship-Based School Management Model to Increase Entrepreneurship Interest of Vocational Education Students - Saputri, Annisa; Yulastri, Asmar; Yuliana, Yuliana; Saputra, Hadi Kurnia; Fiandra, Yudha Aditya (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
The aim of this research is to determine the perceptions of students, teachers and school principals regarding the entrepreneurship-based management model that is planned to be implemented at SMK Negeri 1 Lembah Melintang and to find out their hopes regarding increasing students' interest in entrepreneurship. Qualitative research with a case study approach. Data sources were obtained through observation and interviews with students, teachers and principals of SMK Negeri 1 Lembah Melintang. The entrepreneurship-based management model is believed to be able to create a learning environment that is conducive to the development of an entrepreneurial spirit. However, commitment and support from all stakeholders is needed, including improving facilities, to achieve the goal of increasing students' interest in entrepreneurship. Implementing a comprehensive entrepreneurship-based management model along with strengthening infrastructure support can motivate students' interest in entrepreneurship at SMK Negeri 1 Lembah Melintang.